Space and Place in Alice Munro's Fiction: A Book with Maps in It - Lorre-Johnston, Christine (European studies in North American literature and culture, 2018)
New essays engaging with the developing field of literary geography to devote attention to the ""regional"" settings of Munro's stories and how they affect her characters' development or stasis.